Mammographic density among indigenous women in forested areas in the state of Amapá, Brazil: a cross-sectional study - Secco, José Mauro; Elias, Simone; Carvalho, Cristina Valletta de; Silva, Ismael Dale Cotrim Guerreiro da; Campos, Kátia Jung de; Facina, Gil; Nazário, Afonso Celso Pinto (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: There is no register of breast cancer cases among indigenous populations in Brazil. The objective here was to evaluate the association of clinical and demographic characteristics with mammographic density among indigenous women. DESIGN AND SETTING: Cross-sectional analytical study conducted in indigenous territories in the state of Amapá, Brazil. METHODS: Women were recruited from three indigenous territories and underwent bilateral mammography and blood collection for hormonal analysis. They were interviewed with the aid of an interpreter. Mammographic density was calculated using computer assistance, and was expressed as dense or non-dense. RESULTS: A total of 137 indigenous women were included in this study, with an average age of 50.4 years, and an average age at the menarche of 12.8 years. Half (50.3%) of the 137 participants had not reached the menopause at the time of this study. The women had had an average of 8.7 children, and only two had never breastfed. The average body mass index of the population as a whole was 25.1 kg/m2. The mammographic evaluation showed that 82% of women had non-dense breasts. The clinical characteristics associated with mammographic density were age (P = 0.0001), follicle-stimulating hormone (FSH) (P < 0.001) and estrogen levels (P < 0.01). CONCLUSIONS: The majority of the indigenous women had non-dense breasts. Age, menopausal status and FSH and estrogen levels were associated with mammographic density.